Minimally Invasive Surgical Management of Early-Stage Cervical Cancer. Issue 4 (May 2015) - Garabedian, Charles; Merlot, Benjamin; Bresson, Lucie; Tresch, Emmanuelle; Narducci, Fabrice; Leblanc, Eric
<x xml:space="preserve">Abstract</x> Objectives The objective of this study was to evaluate the morbidity and the oncologic outcomes of laparoscopic radical hysterectomy in treating early-stage cervical cancer. Methods We included all patients with early-stage cervical cancer (IA, IB1, IIA1, and IIB), as assessed by the Federation International of Gynecology and Obstetrics staging criteria, undergoing laparoscopic radical hysterectomy from January 1999 to December 2013 in our center. Morbidity was classified according to the Clavien and Dindo classification. Results A total of 170 patients were included in which 7 patients were in stage IA2, 150 in IB1, 2 in IIA, and 7 in IIB. The mean operation time was 256 minutes (67–495 minutes). Fourteen severe perioperative complications (8.2%) occurred, in which 5 patients (2.9%) required conversion to an open procedure: 3 bowel injuries, 3 hemorrhages, 2 ureteral injuries, 3 bladder injuries, 2 severe adhesions, and 1 intolerance to the Trendelenburg position. Fourteen patients (8.2%) presented with 1 severe postoperative complication (grade III or more). Two factors appeared as independent risk factors for perioperative and/or postoperative complications: the tumor size (odds ratio, 1.128; 95% confidence interval, 1.054–1.207) and operative time (odds ratio, 1.0116; 95% confidence interval, 1.003–1.020). In a median follow-up of 47.7 months, the 5-year overall survival was 94.1% (range, 88.1%–97.3%), and the 5-year disease-free survival was 88.8% (range, 81.0%–92.6%). Conclusions The laparoscopic approach was favorable for both perioperative and postoperative morbidity. With the advantage of minimal invasiveness, laparoscopic treatment by experienced surgeons is an alternative for early-stage cervical cancer with correct long-term survival outcomes. Mini-invasive surgery could be the standard in early-stage cervical cancer.